QUALITY IN SMART CITY INFRASTRUCTURE SERVICE INDICATORS - Jumanova, Zukhra Kholbaevna (Mental Enlightenment Scientific-Methodological Journal, 2024)
This article examines a number of relevant areas that help address smart city development. They are caused by the acceleration of digitization of all spheres of modern society, urbanization of regions. In this work, these aspects are highlighted as the main features in the construction of the research tree. The scientific novelty of the obtained result is in the systematization of research on the topic of smart cities and the identification of the main development trends in this field of knowledge.